Perubahan Karakter Agronomis Beberapa Varietas Padi Terhadap Cekaman Rendaman Diberbagai Kondisi Kekeruhan Air - Gribaldi Gribaldi; Nurlaili Nurlaili (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2015)
Plants which experienced the stress immersion of photosynthesis and its respiration were hampered, as a result of gas diffusion and penetration of low light. Penetration of light that can be captured by the plant which experienced the stress immersion is highly depending on the turbidity of water and the height of immersion. Some rice varieties have different growth responses to the stress immersion at various water turbidity. This study aims to obtain varieties that are tolerant to stress immersion in various conditions of water turbidity. The experimental design used in this research is completely randomized design arranged in a factorial with two factors treatments and three replications. The first factor is rice varieties consists of IR 64 (V1), Inpara 3 (V2), and Inpara 5 (V3). The second factor is the turbidity of water immersion consists of without an immersion (K0), immersion in pure water (K1), immersion in Â½ water turbid (K2), immersion in water turbid (K3). Submersion did on 7hst for 7 days. The results showed that rice crops which experienced the stress immersion in various water turbidity showed a response to agronomic characterâ€™s changing which is different, Inpara 5 varieties tend to be more tolerant of stress immersion in various water turbidity, the more turbid water immersion, the greater damage to the rice crop and the lower production of grain produced per hectare